Medium-term effects of Italian smoke-free legislation: findings from four annual population-based surveys. Issue 7 (15th March 2009) - Tramacere, I; Gallus, S; Fernandez, E; Zuccaro, P; Colombo, P; La Vecchia, C
Abstract : Background: Italy was the first large country to ban smoking in all indoor public places, including restaurants and bars. The aim of this study was to quantify, 3 years after the law came into force, the effects of the smoking ban in terms of observance of the legislation and change of habits. Methods: Data were considered from four representative surveys on smoking, conducted between 2005 and 2008 on a total of 12 245 individuals (5906 men and 6339 women) aged 15 years or over. Results: In 2008, more than 80% of Italians (more than 90% in northern Italy) had the perception that the smoking ban was respected in bars/cafes and restaurants, despite a slight reduction since 2005. In all the surveys combined, 75% of the Italian population reported that the smoking ban was respected in workplaces. Overall, approximately 10% of Italians reported that, after the implementation of the tobacco regulation, they went to bars/cafes and restaurants more frequently, and approximately 7% less frequently, than before. Conclusion: The study shows that in Italy the smoke-free legislation did not affect the business of restaurants and bars, and remains widely respected 3 years after the law came into force.